Cultural Identity and Social Capital in Italy - Daniel Sgroi; Michela Redoano; Federica Liberini; Ben Lockwood; Emanuele Bracco; Francesco Porcelli (Institute of Labor Economics (IZA), 2020)
In a pre-registered experiment involving 1,547 subjects across three Italian cities we exploit regional variation in background, language and diet to investigate the relationship between cultural identity, trust and cooperation. Subjects with relatives (especially maternal grandmothers) who originate in the north of Italy, and who share common cultural characteristics, contributed 15% more in a public goods game, displayed greater "social capital" such as trust in the government and more willingness to pay taxes, than did those whose language and diet identified them as being from the south. On the other hand, self-reported identity, a mainstay of the survey literature, had no predictive power. This highlights the importance of identity but only when it is measured appropriately.
Keywords: Z13; D91; C83; C93; 330; social capital; trust; identity; language; experiments